2017
DOI: 10.3390/ani7070055
|View full text |Cite
|
Sign up to set email alerts
|

Ranging Behaviour of Commercial Free-Range Broiler Chickens 2: Individual Variation

Abstract: Simple SummaryAlthough the consumption of free-range chicken meat has increased, little is known about the ranging behaviour of meat chickens on commercial farms. Studies suggest range use is low and not all chickens access the range when given the opportunity. Whether ranging behaviour differs between individuals within a flock remains largely unknown and may have consequences for animal welfare and management. We monitored individual chicken ranging behaviour from four mixed sex flocks on a commercial farm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…(2018c) reported that, despite all hens being in the same aviary, the number of transitions between aviary tiers and the winter garden was highly specific to individual animals, with total daily transitions ranging from 20 to 159. Similar patterns of differential movement patterns were observed in terms of movement between inside and outside barn areas (Y. Gómez, unpublished work; Gebhardt-Henrich et al., 2014 ; Larsen et al., 2017 ; Taylor et al., 2017 ). In this scenario, although all birds are contained within the same housing system, the differential activity levels would be expected to result in substantially different bone loading and consequent bone strength.…”
Section: Additional Explanations For Kbf Susceptibilitymentioning
confidence: 90%
“…(2018c) reported that, despite all hens being in the same aviary, the number of transitions between aviary tiers and the winter garden was highly specific to individual animals, with total daily transitions ranging from 20 to 159. Similar patterns of differential movement patterns were observed in terms of movement between inside and outside barn areas (Y. Gómez, unpublished work; Gebhardt-Henrich et al., 2014 ; Larsen et al., 2017 ; Taylor et al., 2017 ). In this scenario, although all birds are contained within the same housing system, the differential activity levels would be expected to result in substantially different bone loading and consequent bone strength.…”
Section: Additional Explanations For Kbf Susceptibilitymentioning
confidence: 90%
“…There is a growing body of literature that recognises the importance of allowing chickens to express their natural behaviour by providing outdoor access [18][19][20][21][22][23][24]. However, reports of the effects on the behaviour and welfare of commercial-line broiler chickens raised in housing conditions with outdoor access in the tropics are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies that used radio frequency data transmission were classified as RFID and were present in four papers (7.0%). These ITs were used to evaluate broilers' behaviour in free-range systems: monitoring their location [71], evaluating their ranging behaviour [72,73], and assessing if a RFID tag placed on their back could interfere with their behaviour [45].…”
Section: Radio Frequency Identificationmentioning
confidence: 99%
“…Taylor et al [73] 2017 Australia, Switzerland RFID used to track individual ranging behaviour in free-range systems.…”
Section: Broiler Farmmentioning
confidence: 99%